Specific PCR detection of Fusarium oxysporum f. sp. raphani: a causal agent of Fusarium wilt on radish plants. (3rd July 2017) - Kim, H.; Hwang, S.‐M.; Lee, J.H.; Oh, M.; Han, J.W.; Choi, G.J.
Abstract: Fusarium oxysporum, a causal agent of Fusarium wilt, is one of the most important fungal pathogens worldwide, and detection of F. oxysporum DNA at the forma specialis level is crucial for disease diagnosis and control. In this study, two novel F. oxysporum f. sp. raphani ( For )‐specific primer sets were designed, FOR1‐F/FOR1‐R and FOR2‐F/FOR2‐R, to target FOQG_17868 and FOQG_17869 ORFs, respectively, which were selected based on the genome comparison of other formae speciales of F. oxysporum including conglutinans, cubense, lycopersici, melonis, and pisi . The primer sets FOR1‐F/FOR1‐R and FOR2‐F/FOR2‐R that amplified a 610‐ and 425‐bp DNA fragment, respectively, were specific to For isolates which was confirmed using a total of 40 F. oxysporum isolates. From infected plants, the FOR2‐F/FOR2‐R primer set directly detected the DNA fragment of For isolates even when the radish plants were collected in their early stage of disease development. Although the loci targeted by the For ‐specific primer sets were not likely involved in the pathogenesis, the primer set FOR2‐F/FOR2‐R is available for the determination of pathogenicity of radish‐infecting F. oxysporum isolates. This study is the first report providing novel primer sets to detect F. oxysporum f. sp. raphani . Significance and Impact of the Study: Because plant pathogenic Fusarium oxysporum has been classified into special forms based on its host specificity, identification of F. oxysporum usually requires a pathogenicity assay as well as knowledge of the morphological characteristics. For rapid and reliable diagnosis, this study provides PCR primer sets that specifically detect Fusarium oxysporum f. sp. raphani ( For ) which is a devastating pathogen of radish plants. Because one of the primer sets directly detected the DNA fragment of For isolates from infected plants, the specific PCR method demonstrated in this study will provide a foundation for integrated disease management practices in commodity crops. Abstract : Significance and Impact of the Study: Because plant pathogenic Fusarium oxysporum has been classified into special forms based on its host specificity, identification of F. oxysporum usually requires a pathogenicity assay as well as knowledge of the morphological characteristics. For rapid and reliable diagnosis, this study provides PCR primer sets that specifically detect Fusarium oxysporum f. sp. raphani ( For ) which is a devastating pathogen of radish plants. Because one of the primer sets directly detected the DNA fragment of For isolates from infected plants, the specific PCR method demonstrated in this study will provide a foundation for integrated disease management practices in commodity crops.